2013
DOI: 10.1111/beer.12013
|View full text |Cite
|
Sign up to set email alerts
|

Firm performance, corporate ownership, and corporate social responsibility disclosure in China

Abstract: The existing literature provides conflicting results on the association between firm performance and corporate social responsibility (CSR) disclosure. This paper empirically examines the effect of firm performance on CSR disclosure in terms of disclosure frequency and quality among Chinese listed firms and the possible mediating effect of corporate ownership on the relationship between firm performance and CSR disclosure. Our findings show that better‐performing firms are more likely than worse‐performing ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
167
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(181 citation statements)
references
References 80 publications
(157 reference statements)
9
167
3
2
Order By: Relevance
“…This correlation has often been proposed in theoretical and empirical research on CSR, but there is no consensus on whether such a correlation is characterized as positive or negative. That said, some management theories postulate that CSR disclosure is positively correlated to corporate profitability [3,20,36] because better performing companies are more likely to engage with CSR, and because firms engaging with CSR are more likely to gain indirect strategic or financial benefits [47,67]. Other studies [15,18,53] at the international level also show that there is a positive correlation between profit and CSR activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation has often been proposed in theoretical and empirical research on CSR, but there is no consensus on whether such a correlation is characterized as positive or negative. That said, some management theories postulate that CSR disclosure is positively correlated to corporate profitability [3,20,36] because better performing companies are more likely to engage with CSR, and because firms engaging with CSR are more likely to gain indirect strategic or financial benefits [47,67]. Other studies [15,18,53] at the international level also show that there is a positive correlation between profit and CSR activities.…”
Section: Discussionmentioning
confidence: 99%
“…All that said, this may not be the case for China. Previous studies have shown that Chinese companies tend to be more concerned with whether or not they should release CSR reports and, if so, how much information should be contained within the reports [47].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…e initial studies focused on identifying the stage of CSP disclosure, its relationship with strategy, and a description, observation, and critical evaluation of disclosure practices (Bowman & Haire, 1976;Brockho , 1979;Dierkes, 1979;Guthrie & Parker, 1989;Preston, 1981;Schreuder, 1979;Ullmann, 1979). e studies subsequently addressed the relationship between disclosure and di erent motivating factors, such as stakeholder power and pressure, culture, reputation, and corporate governance mechanisms, among others (Bayoud & Kavanagh, 2012;Mio, Venturelli & Leopizzi, 2015;Haji, 2012;Li, Luo, Wang & Wu, 2013; Van der Laan, Adhikari & Tondkar, 2005). D-CSP is one of the ways for an organization to seek legitimacy in its actions and can be considered as an instrument for making social performance visible to stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2013) explain why SoEs engage more in social responsibility compare to Non-SoEs. Further, they argue that the state as owner often has goals that are different from those of private shareholders.…”
Section: Stakeholder Theorymentioning
confidence: 95%
“…That is because ownership by the government indirectly means that the company is owned by the public at large. Gao (2011) Table 1 summarizes the measurement of the dependent, independent, and control variables, including industry type; ownership, profitability, and firm size are variables often used in corporate social responsibility studies (Roberts 1992;Brammer and Millington 2003;Amato and Amato 2007;Bartkus et al 2002;Ghazali, 2007;Li et al 2013). The amount monetery corporate community contributions made by firm which is self-reported in annual and/or sustainability reports.…”
Section: Stakeholder Theorymentioning
confidence: 99%